2015
DOI: 10.1016/j.seizure.2015.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and acute outcomes of ICU patients with initial presentation of seizure

Abstract: Patients presenting to the ED with and without SE requiring ICU admission may have similar acute outcomes, yet differ in risk factors and seizure etiologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The relevance of seizures at presentation and relationship with in-hospital mortality was evaluated in a retrospective cohort study that recruited 247 patients presenting with seizures to the emergency department and admitted to the ICU for treatment. 14 In this subgroup of patients, ICH was detected as a possible underlying cause of the seizures in 36 of 247 patients (14.5%). Overall, in-hospital death occurred in 7.7%.…”
Section: Risk Stratification and Neurocritical Care Or Intensive Carementioning
confidence: 81%
See 2 more Smart Citations
“…The relevance of seizures at presentation and relationship with in-hospital mortality was evaluated in a retrospective cohort study that recruited 247 patients presenting with seizures to the emergency department and admitted to the ICU for treatment. 14 In this subgroup of patients, ICH was detected as a possible underlying cause of the seizures in 36 of 247 patients (14.5%). Overall, in-hospital death occurred in 7.7%.…”
Section: Risk Stratification and Neurocritical Care Or Intensive Carementioning
confidence: 81%
“…After screening for eligibility, 37 articles were excluded and 14 articles were selected ( Fig. 1) and categorized into the following four subcategories: risk stratification and NCC or ICU treatment, [13][14][15][16] haemodynamic management, 17-22 mechanical ventilation, 23 24 and pharmacological neuroprotection 25 26 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The seven studies that were not suitable for prevalence‐of‐intubation pooling had cohorts that consisted entirely of those that were intubated, making a calculation of prevalence impossible . A comprehensive listing of the 46 articles with a description of study characteristics, prevalence‐bias assessment, and intubation prevalence are shown in Table S1 …”
Section: Resultsmentioning
confidence: 99%
“…Although the patients’ complaints about having seizures are frequently seen in the ED, they vary widely in terms of frequency, severity, and prognostic significance. 1 , 2 Seizure constitutes 1% of annual emergency admissions in the USA. 3 It has been reported that 28% of patients with epilepsy admit to EDs for treatment purposes every year.…”
mentioning
confidence: 99%